Inclusive employment accommodations for persons with disabilities - Guinto, Edward Agustin (2007)
One hundred seventeen business enterprises from the roster of member-companies of the Personal Management Association of the Philippines (PMAP) participated in this study that analyzed the willingness of company-respondents to make job accommodations for persons with disabilities (PWDs). They responded to a survey of their perceptions and attitudes on 5 aspects of inclusive employment, namely, job application, physical environment, benefits and privileges, support facilities, and administrative support. Their positive attitude towards employing PWDs was revealed. The study tested the relationship between the different forms of job accommodations and company demographics and attitudes. Policies that aim to boost the willingness of companies to make job accommodations for PWDs should be done.